A Scope of Chiral Cyclopropanations of Various α-functionalized Diazoketone Derivatives with Styrene Catalyzed by p-Nitro Ru(II)-diphenyl- Pheox Complex - Chi, Le Thi L.; Iwasa, Seiji (Letters in Organic Chemistry, 2023)
Following the success of the first intermolecular cyclopropanations of diazo acetoxy acetone with olefins using a novel p-nitro-Ru(II)-diphenyl-Pheox catalyst, other α-functionalized diazoketones have synthesized using the same reaction conditions. Consequently, chiral cyclopropyl products were formed with excellent yield (up to 87% yield), high diastereoselectivity (up to 99:1), and high enantioselectivity (up to 90% ee).
Keywords: Asymmetric synthesis